Application of Mixture Tuned Matched Filtering on ASTER Data for Hydrothermal Alteration Mapping Related to Porphyry Cu Deposits in Jabal-Barez Ranges, Kerman Copper Belt, Iran - S. J. Yousefi; H. Ranjbar; S. Alirezaei; S. Dargahi (Journal of Sciences, Islamic Republic of Iran)
The study area is located in Jabal-Barez Ranges, southeastern part of Kerman Copper Belt (KCB), where the porphyry copper mineralization such as Kerver occurs. This article deals with the enhancement of hydrothermal alteration minerals for exploration of porphyry Cu mineralization, and differentiates intense hydrothermal alteration zones from those with low intensity. Shortwave Infrared (SWIR) bands of ASTER data were used for mineral enhancement. The spectra of representative alteration mineral assemblages consisting of sericite + illite, kaolinite + montmorillonite and epidote + chlorite were extracted from SWIR bands of ASTER. The spectra were applied for mineral discrimination using Mixture Tuned Matched Filtering (MTMF) technique. The image processing results were verified using field observation, spectral measurements, thin section and X-ray diffraction studies of the samples. Findings exhibit ASTER capability to discriminate different alteration zones. Findings also significantly show the role of MTMF algorithm as a useful technique for mineral exploration.